Concentrated Bioshell Calcium Oxide (BiSCaO) Water Kills Pathogenic Microbes: Characterization and Activity - Shingo Nakamura; Masayuki Ishihara; Yoko Sato; Tomohiro Takayama; Sumiyo Hiruma; Naoko Ando; Koichi Fukuda; Kaoru Murakami; Hidetaka Yokoe (Molecules, 2020)
Bioshell calcium oxide (BiSCaO) exhibits deodorizing properties and broad microbicidal activity. In this study, we examined possible utility of BiSCaO Water for that purpose. BiSCaO Water was prepared by adding 10 wt% BiSCaO to clean water and gently collecting the supernatant in a bottle. The same volume of clean water was gently poured onto the BiSCaO precipitate and the supernatant was gently collected in a bottle; this process was repeated fifty times. The produced BiSCaO Water contained nanoparticles (about 400–800 nm) composed of smaller nanoparticles (100–200 nm), and was colorless and transparent, with a pH > 12.7. In vitro assays demonstrated that BiSCaO Water eliminated more than 99.9% of influenza A (H1N1) and Feline calicivirus, Escherichia coli such as NBRC 3972 and O-157:H7, Pseudomonas aeruginosa, Salmonella, and Staphylococcus aureus within 15 min. We compared BiSCaO Water with the other microbicidal reagents such as ethanol, BiSCaO, BiSCa(OH)2 suspensions, povidone iodine, NaClO, BiSCaO dispersion and colloidal dispersion with respect to deodorization activity and microbicidal efficacy. The results showed that BiSCaO Water was a potent reagent with excellent deodorization and disinfection activities against pathogenic bacteria and viruses (including both enveloped and nonenveloped viruses).